2021
DOI: 10.3389/fcell.2021.689533
|View full text |Cite
|
Sign up to set email alerts
|

Current Pharmacological Strategies for Duchenne Muscular Dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a lethal, X-linked neuromuscular disorder caused by the absence of dystrophin protein, which is essential for muscle fiber integrity. Loss of dystrophin protein leads to recurrent myofiber damage, chronic inflammation, progressive fibrosis, and dysfunction of muscle stem cells. There is still no cure for DMD so far and the standard of care is principally limited to symptom relief through glucocorticoids treatments. Current therapeutic strategies could be divided into two li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 261 publications
(327 reference statements)
0
40
0
Order By: Relevance
“…This work showed that the anti-oxidant effects of these herbal compounds can be effective at reducing oxidative stress. In a recent review of DMD therapeutics, a meta-analysis of gene expression comparisons of other DMD samples showed that extracellular matrix (ECM) and cell-to-cell interaction molecules are prime targets for reversing late-stage DMD, which makes logical sense because to restore ambulation, the musculature would need to be strengthened ( 10 ). Stem cells give us the ability to generate and characterize the different cell types affected by DMD, as well as the ability to perform high-throughput drug screens, paving the way toward patient-specific treatment programs.…”
Section: Human Stem Cells Provide Cell Type- and Disease-specific Ins...mentioning
confidence: 99%
See 1 more Smart Citation
“…This work showed that the anti-oxidant effects of these herbal compounds can be effective at reducing oxidative stress. In a recent review of DMD therapeutics, a meta-analysis of gene expression comparisons of other DMD samples showed that extracellular matrix (ECM) and cell-to-cell interaction molecules are prime targets for reversing late-stage DMD, which makes logical sense because to restore ambulation, the musculature would need to be strengthened ( 10 ). Stem cells give us the ability to generate and characterize the different cell types affected by DMD, as well as the ability to perform high-throughput drug screens, paving the way toward patient-specific treatment programs.…”
Section: Human Stem Cells Provide Cell Type- and Disease-specific Ins...mentioning
confidence: 99%
“…As more cellular processes are disrupted, more evidence of cellular dysfunction is exhibited that can be detected in the form of higher levels of serum biomarkers like creatine kinase and myoglobin as signs of muscle wasting, and TNF-α, IFN-γ, IL-5 and IL-6 as signs of chronic inflammation (6)(7)(8)(9). Therapeutic efforts for DMD are therefore divided between targeting (i) the underlying cause of DMD, loss of dystrophin, or (ii) targeting a secondary pathology (10).…”
Section: Introductionmentioning
confidence: 99%
“…A majority of patients become nonambulatory by age 15 years, require ventilatory support by age 20, and up to 60% of patients die by age 30 from progressive cardiac and respiratory complications [ 9 ]. Genetic testing in the newborn (NB) period is typically not considered unless family history suggests risk of disease; however, recent and emerging treatments for DMD [ 10 ] underscore the need to evaluate the potential importance of presymptomatic identification and access to early treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As conventional drugs are not effective for the treatment of DMD, this strategy is becoming a more common alternative. This group comprises DNA-editing therapy (CRISPR-Cas9; usually exon manipulation) ( Long et al, 2014 ; Li et al, 2015 ; McTague et al, 2021 ), gene-addition therapy (microdystrophin with the AAV vector) ( Yoshimura et al, 2004 ; Duan, 2018 ), RNA-manipulation therapy (Eteplirsen, Golodirsen, Viltolarsen, Casimersen, ASO-cocktail therapy, and RNA-editing therapy), and cell therapy ( Motohashi et al, 2019 ; Yao et al, 2021 ). Since the lack of functional dystrophin causes DMD, restoring dystrophin is an apparent therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%